Epicardial fat inflammation response to COVID‐19 therapies. Issue 9 (3rd August 2021) - Iacobellis, Gianluca; Malavazos, Alexis Elias; Basilico, Sara; Tresoldi, Silvia; Rinaldo, Rocco Francesco; Dubini, Carola; Capitanio, Gloria; Serpi, Francesca; Schiaffino, Simone; Oliva, Omar Alessandro; Cariati, Maurizio; Morricone, Lelio; et al.
Abstract: Objective: Adipose tissue plays a role in the novel coronavirus disease 2019 (COVID‐19). Epicardial adipose tissue (EAT), a unique visceral fat, presents with a high degree of inflammation in severe COVID‐19. Whether and how adipose tissue may respond to the COVID‐19 therapies is unknown. Methods: The difference in computed tomography‐measured EAT and subcutaneous (SAT) attenuation, defined as mean attenuation expressed in Hounsfield units (HU), was retrospectively analyzed in 72 patients (mean [SD] age was 59.6 [12.4] years, 50 patients [69%] were men) at the hospital admission for COVID‐19 and 99 days (interquartile range = 71‐129) after discharge. Results: At the admission, EAT‐HU was significantly correlated with blood glucose levels, interleukin 6, troponin T levels, and waist circumference. EAT‐HU decreased from −87.21 (16.18) to −100.0 (11) ( p < 0.001), whereas SAT‐HU did not change (−110.21 [12.1] to −111.11 [27.82]; p = 0.78) after therapy. Changes in EAT‐HU (expressed as ∆) significantly correlated with dexamethasone therapy ( r = −0.46, p = 0.006) and when dexamethasone was combined with tocilizumab ( r = −0.24, p = 0.04). Conclusions: Dexamethasone therapy was associated with significant reduction of EAT inflammation in COVID‐19 patients, whereas SAT showed no changes. Anti‐inflammatory therapies targeting visceral fat may be helpful in COVID‐19.